Battling Angels and Golden Orange Blossoms: Thai Television and/as the Popular Public Sphere - Farmer, Brett (Television Histories in Asia: Issues and Contexts, 2015)
On 19 September 2006, the fi rst indication many people in Thailand received that the country was undergoing another military coup d’ é tat, the eighteenth such putsch since 1932, was when the nation’s six free-to-air television networks suddenly suspended regular programming and, channel by channel, started to broadcast a generic mix of royal news and light entertainment (Connors and Hewison 2008). Final confi rmation came again via television later that evening in the form of an offi cial announcement, broadcast at regular intervals across all stations from a central feed, in which the armed commanders in chief behind the coup – the awkwardly titled ‘Administrative Reform Group under the Democratic System with the King as the Head of State’ – explained apologetically that they had temporarily taken control of the nation’s airwaves, as indeed of the nation, exhorting viewers to remain calm and reassuring them that normalcy would soon be restored, at which point broadcasting reverted to the same steady flow of innocuous entertainment programming. For all its exceptional gravity, the 2006 coup’s strategic blend of direct state interventionist control of broadcasting combined with a more indirect use of escapist entertainment as populist pacifi er is arguably a structural characteristic of Thai television history writ large.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Thaïlande (corpus analysé); _Nettoyé

Dramatizing the Nation: Television, History and the Construction of Singaporean Identity - Tay, Jinna (Television Histories in Asia: Issues and Contexts, 2015)
Television dramas, both serials and series, have been a long-term recruiter of large-scale national audiences for television broadcasters as they are potentially able to speak to their audience in affective and imaginative ways (Chan 2011 ; Sun and Gorfi nkel 2014). Usually it is the locally produced drama that resonates most with a national audience, the familiarity of the setting and context often carrying signifi cant implications for social and sometimes political life (Blandford et al. 2011 , Chan 2011 ). These television texts can pick up on popular strands of discourses in the public sphere and succeed in establishing a form of dialogue with audiences; in the instances examined in this chapter, this dialogue is about the formation of national identities or citizenships. There is good reason, then, for broadcasters and governments to attempt to use television drama to educate and persuade, although Sugg and Power ( 2011 : 26-7), long-term drama producers at the BBC World Service Trust, warn that for dramas to succeed in this manner, they first have to be entertaining, otherwise they are unlikely to generate an audience in the fi rst place. Audiences are not easily fooled and can sniff out the difference between being entertained and being preached at in a didactic way. This chapter deals with a period in the history of Singapore where television historical drama played a signifi cant role in creating a national past upon which the promotion of a distinctive national identity might be based. In addition to a consideration of a selection of drama series themselves, the chapter draws upon interviews where viewers are encouraged to share their memories of these dramas, and the part they played in the construction of a Singaporean identity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Working Women and Romance on Japanese Television Dramas: Changes since Tokyo Love Story - Freedman, Alisa (Television Histories in Asia: Issues and Contexts, 2015)
Since their development in their current format in the early 1990s as a means to attract female viewers in their twenties, Japanese prime-time television dramas-known commonly as ‘ dorama ’ 1 —have featured working women. Even police procedurals, medical dramas, and serials based on ‘ shojo manga ’ (graphic novels for girls) depict women working outside the home. The dorama most watched by Japanese audiences older than age 25, and those that continue to attract global fans, present the daily lives of independent women working in Tokyo. The protagonists enact fantasies about female professionals while depicting real issues facing the larger generations they represent. Viewers may not want to be these characters, but they can see aspects of themselves in them.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Japon (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Unpacking Multiculturalism and Islam in Malaysia: State–Corporate Television Celebrations of Bangsa Malaysia - Khattab, Umi (Television Histories in Asia: Issues and Contexts, 2015)
This chapter presents a critical analysis of media and change in postcolonial Malaysia, a South-East Asian nation of 29  million multicultural people, with a focus on the role of television in the nation’s transformation following independence from British rule in 1957. Despite having inherited the basic democratic institutions of the British political tradition, Malaysia continues to debate the transition from soft authoritarianism to democracy (Means 1996 :  103). Since 1957, Malaysia has been led by a single political party, the Barisan Nasional (BN). While the BN is a coalition of three major ethnic-based political groups, the United Malays National Organisation (UMNO), Malaysian Chinese Association (MCA) and the Malaysian Indian Congress (MIC), it is, in effect, a symbol of Malay-Muslim supremacy (Ketuanan Melayu). UMNO, the dominant group within the party, has, since its formation, aspired to uphold Malay culture as national culture and Islam as the offi cial religion for the country. From the fi rst general elections in 1959 until the 2008 general elections, the BN held two-thirds of the 222 seats in the Dewan Rakyat (House of Representatives). Malaysian media scholar Karthigesu ( 1987 , 1994 ) contends this was largely due to the role of public television, which was launched and promoted by government itself, broadcasting in its colonial service model. In fact, the arrival of state television in 1963 coincided with the formation of the Federation of Malaysia (Moten and Mokhtar 2013 ). In this chapter I argue that television has been pivotal in shaping and transforming the political and cultural landscape of Malaysia as the medium evolved from a strictly national to a loosely global and then fluidly trans-local orientation. While television fi rst enabled the BN to hold its two-thirds majority and build the nation premised on Malay supremacy policies, it subsequently played a part in weakening the BN’s grip over the multiethnic electorate as the UMNO Ketuanan Melayu ideology, layered deep beneath the powdered face of television, surfaced in the digital media era.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Malaisie (corpus analysé); _Nettoyé

Shifts in Korean Television Music Programmes: Democratization, Transnationalization, Digitalization - Jung, Sun (Television Histories in Asia: Issues and Contexts, 2015)
Korea was the fifteenth country in the world to start television broadcasting when it first launched in Seoul in 1956. Since then, the structure, content and policies concerning Korean television have continuously transformed, due largely to changing contextual circumstances such as wide-ranging socio-political democratization and the rise of the neoliberal global economic system and digital technologies. Up until the 1980s, the oligopolistic structure of the two public broadcasting networks  – Korean Broadcasting System (KBS) and Munhwa Broadcasting Corporation (MBC)  – dominated the broadcasting market. However the landscape has dramatically changed since the early 1990s, with 11 newly launched commercial terrestrial broadcasting channels (including Seoul Broadcasting System (SBS) in December 1991) and 153 cable channels when the multichannel television era began (Jin 2005 : 1). A digital satellite television system called Skylife was launched in March 2002, and airs 176 channels at the time of writing. Such changes stem from the shift in the domestic political climate where liberalization and privatization were promoted in assertively practiced neoliberal reform movement in the early 1980s, as well as changes in the global cultural industry environments based largely on globalization and the development of digital technologies. This chapter explores democratization, transnationalization and digitalization, three active factors within Korean television broadcasting by analysing changes and shifts in popular music programmes.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); _Nettoyé

The Television of Intervention: Mediating Patron–Client Ties in the Philippines - Corpus Ong, Jonathan (Television Histories in Asia: Issues and Contexts, 2015)
Similar to the other countries discussed in this volume, elite dominance over mass media has been a main characteristic of Filipino history. Foreign-educated Filipino intellectuals from wealthy families founded the early periodicals that demanded reform and/or independence from Spanish colonization in the late nineteenth century (Anderson 1983 ). Today, ‘old rich’ landowning families own and operate television networks, radio stations, and newspapers not only as part of prestigious and profi table media conglomerates, but also in connection with their interests in industries as varied as oil and agriculture to insurance, shipping, and mining.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Philippines (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Cultural Polysemy and Vernacular Cosmopolitanism in the Theme Songs of Hong Kong Television Dramas - Kai Khiun, Liew (Television Histories in Asia, 2015)
In 1980, Hong Kong’s commercial Television Broadcast Limited (TVB) television drama The Bund ( 上海滩 ) was popularly received in the city as well as in South-East Asia and the broader Chinese diaspora. Set in the cosmopolitan treaty port of Shanghai in the 1920s, The Bund revolves around the violent ascent of a coolie (Ray Lui) and a disillusioned student activist (Chow Yun-Fat) to become prominent mobsters. Not only were two sequels made within that year, but this historical gangster drama has been repeatedly resurrected in television dramas and fi lms, including Chow’s redux, The Last Tycoon ( 大上海 ), three decades later in 2012. From karaoke lounges to social media sites, theme songs of The Bund remain popular more than three decades after the dramas were screened . With music composed by Joseph Koo, lyrics by Wong Jim and sung by Frances Yip, the main and supplementary theme songs refl ected the intimate role of the Hong Kong-based contemporary Cantonese popular music, or Canto-pop, in cultivating a more memorable and enduring televisual culture. With the smooth synchronization of Koo’s classical music with the undulating pitch of Yip, the song articulates the unpredictable tribulations of the changing fortunes in the treaty-port of Shanghai in the interwar years. To a certain extent, it is also a narrative that reminds viewers in Hong Kong and beyond of similar socio-political and historical predicaments.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Taiyu Serial Dramas in Taiwan: A History of Problem-Making - Irene Yang, Fang-Chih (Television Histories in Asia, 2015)
The construction of a problem, be it a crisis or a moral panic, is an attempt of policing and control, for the maintenance of hegemony and authority (Hall et al. 1978 ). A problem emerges as a problem only when it is out of its proper place, just like dirt becomes dirt only when it is not properly placed in the earth. The elimination of dirt is necessary in maintaining the cleanliness of the social order (Douglas 2002 ). In other words, it is the need for a particular social arrangement that constitutes the existence of a problem. Taiyu, the lingua franca of the Taiwanese, became a problem of dialect (called Minnanyu) to be eliminated when the KMT colonial regime moved to Taiwan, building it as a Chinese nation and instituting Mandarin as the national language. Television is central to the building of the Chinese nation. Taiyu serial dramas were broadcast soon after the fi rst network was established in 1962, but have been constructed as the most problematic and debased genre since the early 1970s when the second TV station, CTV (1969), and the third, CTS (1971), were established and used serial drama to compete for profi t. Accusations directed at the poverty of its quality and the vulgarity of the audiences have characterized mainstream criticisms and constructions of Taiyu serial dramas as problems from the 1970s to the present. This chapter investigates not only the how and what but also the why of this problem-construction, as an attempt to understand the power mechanisms at work in struggling for hegemonic control. It charts two historical moments – the 1970s and from the 1990s to the present – when language has played a signifi cant role in the articulations of serial dramas as problems and explores the changing political, economic and cultural forces that situate them as problems worthy of discussion. I argue that the history of this problem-making demonstrates the centrality of Chinese culture in political domination through cultural means, with ethnic/class politics playing a central role in the maintenance of a hierarchical social order. In the 1970s, Chinese culture was used to create ethnic/class divisions within Taiwan while simultaneously creating the illusion of a symbolic whole under the name of the Republic of China. However, since the 1990s, and intensifying after the 2000s, with the entanglement of democratization and neoliberalization in Taiwan and the rise of China, the ethnic/class tension is not just complicated by confl icted national identifi cations and Chinese culturepromoted by both the KMT Party’s Republic of China and the People’s Republic of China, but also for unifi cation purposes. While democratization, which involved the search for Taiwanese identity, led to the rise of Taiyu-based Hsiangtu drama, the neoliberal defi nition of culture as economic resource, which consecrates Chinese culture through capital investment, facilitates this unifi cation process while creating further ethnic/class/national identity divisions within Taiwan. The result is a disparaging of Taiyu-based culture in general and, in particular, Taiyu serial drama as a problem to be reformed.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

Television, Scale and Place-Identity in the PRC: Provincial, National and Global Influences from 1958 to 2013 - Sun, Wanning; Gorfinkel, Lauren (Television Histories in Asia: Issues and Contexts, 2015)
One may argue that Chinese television has already received more than its fair share of attention in the study of Chinese media. As compared with radio and cinema, which developed in the socialist era (1949-78), television has been seen as the dominant medium in the decades of marketization and economic reforms since the late 1970s (Zhu and Berry 2008 ). Television has been studied as a metonym for the ongoing tension and complicity between the Chinese state and the market (e.g., Zhao 1998 ; 2008a) and as a metaphor for the contradictions between a legacy of socialist rhetoric and ethos and a neoliberal market agenda. It is precisely these contradictions that make up what is often referred to as the ‘Chinese characteristics’ (Zhao 2008a; Sun and Zhao 2009 ) of China’s television culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé